2022
DOI: 10.1088/1555-6611/ac687a
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation as a method for microsampling of paint layers

Abstract: It is proposed to use nanosecond laser pulses to obtain microsamples of paint layers with subsequent identification of the substance using Raman microspectroscopy. It is shown that the ablation of the paint layer on the primed canvas is a two-threshold process. The proposed technique can be used to study paintings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recently, we have proposed laser ablation microsampling (LAMS) to replace the traditional scalpel sampling. Focused single-pulse laser radiation has been used to take samples from paper materials [4,5], paint layers on a primed canvas [6], and the surface of fresco painting [7]. It has been shown that the * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proposed laser ablation microsampling (LAMS) to replace the traditional scalpel sampling. Focused single-pulse laser radiation has been used to take samples from paper materials [4,5], paint layers on a primed canvas [6], and the surface of fresco painting [7]. It has been shown that the * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%